Long-term hazard to drinking water resources from landfills - Spillmann, Peter; Dörrie, Timo; Struve, Michael (Thomas Telford, 2009)
Examining each of the main stages of landfill decomposition and using extensive real-scale testing, the book provides a method for measuring the extent to which groundwater and surface water may safely remain in landfill and the associated risks of contamination.